Microstructures and properties of alkali-activated slags with composite activator: Effects of Na2O equivalents - Ji, Xin; Wang, Zhenjun; Wang, Xiaofeng; Zhao, Xin; Zhang, Haibao; Zhang, Tonghuan (Journal of cleaner production, 2024)
Cementitious materials composed entirely of solid waste are expected to replace cement and alleviate environmental pollution problems. Due to limitations in reaction rate and strength, a composite activator comprising NaOH and water glass was employed to investigate the effect of composite activator content (0–12.0% Na2O equivalent) on pore solution pH, hydration products, microscopic morphology, and pore structure of ternary alkali-activated materials prepared by blast furnace slag, desulfurization gypsum and carbide slag. Additionally, the microstructure development results were corroborated through characterization of fluidity, setting time and compressive strength. Results indicate that the reaction process of alkali-activated material accelerates as Na2O equivalent increases from 0 to 8.0%, thereby promoting calcium aluminum silicate gel and hydrotalcite formation, and facilitating the continuous filling of pores, which leads to a dense structure formation. However, excessive gel products are generated on bonded particle surface when Na2O equivalent exceeds 8.0%, hindering polymerization process; meanwhile, the presence of microcracks leads to an increase in macropores (≥10 mm3) proportion resulting in a decrease in compressive strength. Notably, the increase in Na2O equivalent gradually suppresses ettringite formation. Life cycle assessment demonstrates that the preparation of mortar is more environmentally sustainable. Based on the optimal compressive strength, the reduction in global warming, abiotic resource depletion, acidification, and eutrophication potential of mortar compared with cement is 78.7%, 39.7%, 17.9% and 29.2%, respectively. This work contributes to further improving the resource utilization of solid waste, and extending the application of conventional solid waste cementitious materials in the domain of emergency repair engineering.